Cultivating sustained teachers' professional learning within a centralised education system. Issue 1 (2nd January 2018) - Shaari, Imran; Lim, Victor; Hung, David; Kwan, Yew Meng
ABSTRACT: This study investigates how sustained professional learning for teachers within a centralised system was cultivated. Specifically, the sustained professional learning was initiated by officers from the headquarters (HQ) and involved interested teachers across schools in Singapore. Qualitative instruments were used to collect and analyse the data in examining the partnerships perceived by the participants. The enablers responsible to bring about sustained professional learning are proposed. A contribution of this study is to clarify how resources in the HQ and its schools can be bridged. Deliberate bridging of resources is critical particularly at the initial stage of the partnerships. This bridging is made possible through dedicated appointed champions. The appointed champions are passionate about the educational innovations and are willing to invest their time to understand the teachers' needs. This paper argues that the enablers can offer opportunities for lateral networks to be forged within a hierarchical system.